Performance of small grain pastures in Santa Rosa La Pampa.I, Seasonal distribution and total matter yields (Semiárida, 2020)
The seasonal distribution and total dry matter yields, in two years (1988-1989), in seven cultivars 01the small grain pastures were determined. The evaluate cultivars were: oats (Avena sativa L.) cv Don Victor, oats (Avena byzantina C. Koch) cv Millauquén, barley (Hordeum vulgare L.) cv Uñaiché, rye (Secale cereale L.) cvs Choiqué y Naic6, tricepiro (Triticum x Secale x Thinopyron) linea 3/40 and triticale (xTriticosecale Will.) cv Tehuelche. The daily growth rate calculated by clipping into six overlapped sequences with three replications, and total dry matter yield within a completely randomized block design with tour replications. Differences between cultivars were evaluated by ANOVA and test 01Tukey (0=0.05). Rye cv Choiqué showed the highest daily growth rate both years (1988: 51.5±3.7; 1989: 31.3±1.1 kg DM ha-1.d-1 Total dry matter yields 01cultivars was different between years (p0.10). Within year, total dry matter yield of Triticale cv Tehuelche was higher (p
Keywords: small grain pasture; growth curves; yield